2014
DOI: 10.1016/j.quascirev.2013.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial and submarine evidence for the extent and timing of the Last Glacial Maximum and the onset of deglaciation on the maritime-Antarctic and sub-Antarctic islands

Abstract: This paper is the maritime and sub Antarctic contribution to the Scientific Committee for Antarctic Research (SCAR) Past Antarctic Ice Sheet Dynamics (PAIS) community Antarctic Ice Sheet reconstruction. The overarching aim for all sectors of Antarctica was to reconstruct the Last Glacial Maximum (LGM) ice sheet extent and thickness, and map the subsequent deglaciation in a series of 5000 year time slices. However, our review of the literature found surprisingly few high quality chronological constraints on cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
156
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(162 citation statements)
references
References 110 publications
5
156
1
Order By: Relevance
“…Our model results suggests that deglaciation on South Georgia occurred ca. 15 ka, which fits with geomorphological data from the east Antarctic Peninsula where initial retreat was underway by ~18-17.5 ka (Bentley et al, 2014), as 19 well as dates of the onset of peat formation and lake sedimentation at other sub-Antarctic islands, including Kerguelen, Auckland and Campbell, around this time (Hodgson et al, 2014b). …”
supporting
confidence: 81%
See 2 more Smart Citations
“…Our model results suggests that deglaciation on South Georgia occurred ca. 15 ka, which fits with geomorphological data from the east Antarctic Peninsula where initial retreat was underway by ~18-17.5 ka (Bentley et al, 2014), as 19 well as dates of the onset of peat formation and lake sedimentation at other sub-Antarctic islands, including Kerguelen, Auckland and Campbell, around this time (Hodgson et al, 2014b). …”
supporting
confidence: 81%
“…If a large LGM ice cap existed in South Georgia then there is potential for the same to have occurred on other sub-Antarctic islands within a similar climatic context e.g. Kerguelen, and also fits with other models of extensive LGM ice proposed for Heard, Bouvet and the South Orkney Islands (Hodgson et al, 2014b). The presence of an extensive LGM ice cap that reached the continental shelf edge around South Georgia suggests affinity with West Antarctica and the Antarctica Peninsula, which also experienced the most extensive glaciation at the LGM, rather than with Patagonia where the greatest glacial extents were earlier in the Quaternary (Darvill et al, 2015).…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Nougier, 1970). In contrast, Hall (1984) suggested a more extensive ice-cover during the LGM with an equilibrium line altitude of c. 200 m. The timing of the last deglaciation is also not well known and is mainly based on a few basal radiocarbon dates of peat deposits (Hodgson et al, 2014;Van der Putten et al, 2010).…”
Section: Study Areamentioning
confidence: 99%
“…When sea level subsequently rose, peat deposits might have been eroded away. The interplay between eustatic and local sea level changes, however, is poorly constrained on Kerguelen Islands (Hodgson et al, 2014 and references there in). During fieldwork, it was observed that in front of the peat bank big rounded pebbles were present, probably representing an ancient beach level.…”
Section: Fieldworkmentioning
confidence: 99%